2016
DOI: 10.1016/j.virol.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human papillomavirus 16 variants and risk for cervical cancer in Chinese population

Abstract: HPV16 is the most carcinogenic HPV type, but only a minority of HPV16 infections progress to cancer. Intratype genetic variants of HPV16 have been suggested to confer differential carcinogenicity. To investigate risk implications of HPV16 variants among Chinese women, a case-control study was conducted with 298 cervical cancer patients and 85 controls (all HPV16-positive). HPV16 isolates were predominantly of the A variant lineage, and variants of A4 (previously named "Asian") sublineage were common. A4/Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
6
46
1
1
Order By: Relevance
“…These results suggest that HPV16 sublineages A1-3 may be more oncogenic than the sublineage A4 in inducing genital cancers in the Vietnamese population. However, these findings are inconsistent with the previous studies that reported the sublineages A4 and D2 were associated with an increased risk of cervical cancer (11, 14), or that found no significant difference in the distribution of HPV16 sublineages A1-3 and A4 between samples from different stages of cervical intraepithelial neoplasia (15). The discrepancy in the oncogenicity of A4 sublineage between this study and others (11,14,15) may be attributed simply to the regional difference in the ethnic groups.…”
Section: Dicussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results suggest that HPV16 sublineages A1-3 may be more oncogenic than the sublineage A4 in inducing genital cancers in the Vietnamese population. However, these findings are inconsistent with the previous studies that reported the sublineages A4 and D2 were associated with an increased risk of cervical cancer (11, 14), or that found no significant difference in the distribution of HPV16 sublineages A1-3 and A4 between samples from different stages of cervical intraepithelial neoplasia (15). The discrepancy in the oncogenicity of A4 sublineage between this study and others (11,14,15) may be attributed simply to the regional difference in the ethnic groups.…”
Section: Dicussioncontrasting
confidence: 99%
“…However, it is noted that the distributions of the HPV16 sublineages A1-3 and A4 in the Vietnamese genital cancer patients (51.5% and 34.8%, respectively) are similar to those found in Chinese cervical cancer patients (54.0% and 45.6%, respectively) (14). In contrast, the distribution of HPV16 sublineages A1-3 and A4 in Vietnamese women with a normal cytology (13.0% and 82.6%, respectively) was the opposite of that in Chinese women with a normal cytology (67.1% and 32.9%, respectively) (14).…”
Section: Dicussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Compared with women with an HPV16 A1–A3 European lineage infection, women with an HPV16 A4 Asian lineage infection had no significantly increased risk for cervical cancer. However, Hang et al reported that A4 variants appear to predict higher risk of cervical cancer among HPV16-positive women 25 . Thus, further study is required to determine whether A4/Asian variants represent a higher risk for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hoje em dia mais de 99% dos cânceres cervicais contêm a presença do HPV e a proporção associada com o tipo do vírus é diferente entre regiões, mostrando variações demográficas, étnicas e sócioeconômicas (CUBIE, 2013), podendo, dessa forma, afirmar que o HPV é um agente necessário para a doença (BAVA et al 2017;HANG et al, 2016).…”
Section: Câncer Cervicalunclassified